2018
DOI: 10.1007/s12250-018-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Virus NS1′ Protein Antagonizes Interferon Beta Production

Abstract: Japanese encephalitis virus (JEV) is a mosquito-borne virus and the major cause of viral encephalitis in Asia. NS1 0 , a 52-amino acid C-terminal extension of NS1, is generated with a-1 programmed ribosomal frameshift and is only present in members of the Japanese encephalitis serogroup of flaviviruses. Previous studies demonstrated that NS1 0 plays a vital role in virulence, but the mechanism is unclear. In this study, an NS1 0 defected (rG66A) virus was generated. We found that rG66A virus was less virulent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…In this context, it was highly surprising that no obvious type I IFN response was observed in any of the studied brain tissues upon JEV infection. This is most probably due to the capacity of JEV to actively suppress IFN expression as was reported before [34][35][36]. In our experiment, the OAS gene expression could have been activated by a type I IFN-independent mechanism as has been reported for WNV infection [37].…”
Section: Discussionsupporting
confidence: 75%
“…In this context, it was highly surprising that no obvious type I IFN response was observed in any of the studied brain tissues upon JEV infection. This is most probably due to the capacity of JEV to actively suppress IFN expression as was reported before [34][35][36]. In our experiment, the OAS gene expression could have been activated by a type I IFN-independent mechanism as has been reported for WNV infection [37].…”
Section: Discussionsupporting
confidence: 75%
“…The amino acid variations were distributed in three structural proteins (C, PrM, and E) and seven non-structural proteins (NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5) ( Table 1 ). Notably, some non-structural proteins with relatively high numbers of amino acid variations, such as NS1, NS3, and NS5, have been demonstrated to be involved in antagonizing the IFN-I mediated antiviral response in flavivirus[ 33 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, JEV NS19 was demonstrated to inhibit IFN-I production, which contributes to viral virulence (16). However, the exact mechanism remains unclear.…”
mentioning
confidence: 94%
“…Some evidences demonstrated that NS19 has a similar cellular distribution with NS1, and it is able to substitute for NS1 in replication of WNV (11). In addition, increasing reports suggest that NS19 is closely related to virulence (12)(13)(14)(15)(16). Abolishing NS19 in JEV and WNV resulted in the attenuation of viral neuroinvasiveness in mice (12,13).…”
mentioning
confidence: 99%